2000
DOI: 10.1046/j.1439-0450.2000.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antibody‐independent Cellular Cytotoxicity (AICC) of Porcine Neutrophilic Granulocytes by Quantitative Flow Cytometry. Lack of Modulation by Larval Products of Oesophagostomum dentatum

Abstract: After infection of pigs by the larvae of Oesophagostomum dentatum, granulomas are formed around the third-stage larvae in the submucosa of the gut which contain a considerable number of neutrophils. This has no obvious impact on the larvae, which develop to fourth-stage larvae within these granulomas. We therefore asked, whether the products of O. dentatum larvae modulate the functional capacity of porcine neutrophils. The antibody-independent cellular cytotoxicity (AICC) was chosen as a model system. This ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
(57 reference statements)
1
2
0
Order By: Relevance
“…We have chosen flow cytometric methods because of their sensitivity in the detection of even subtle effects on cells. This has been shown by our group in various other studies where cellular responses and function of porcine, bovine and piscine leucocytes have been studied in response to various stimuli invitro as well as ex vivo (Scharsack et al, 2000; Schuberth et al, 2000a, b).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…We have chosen flow cytometric methods because of their sensitivity in the detection of even subtle effects on cells. This has been shown by our group in various other studies where cellular responses and function of porcine, bovine and piscine leucocytes have been studied in response to various stimuli invitro as well as ex vivo (Scharsack et al, 2000; Schuberth et al, 2000a, b).…”
Section: Discussionsupporting
confidence: 54%
“…Bovine lymphoblastoid cells (‘Anna TA1’, Schuberth et al, 2000a) were used as target cells (T). Targets were washed twice in PBS (80 g , 8 min) and adjusted to 1 × 10 6 cells/ml culture medium.…”
Section: Antibody‐independent Cellular Cytotoxicity (Aicc) Of Granulomentioning
confidence: 99%
“…5), demonstrating the destruction of worms by the mobilized cell contingent. The presence of microcysts, although not demonstrated in other studies involving the genus Cooperia (Ransom, 1920;Hung, 1926;Bailey, 1949;Coop et al, 1979;Armour et al, 1987;Oliveira, 2001), was reported by Schuberth et al (2000) in experimental infections of swine with Oesophagostomum dentatum, and the formation of these structures was related to the mobilization of neutrophils and eosinophils. However, in contrast to the present study, no destruction of worms by the cell types in question was observed, and the larvae survived and developed inside the microcysts.…”
Section: Resultsmentioning
confidence: 69%